Remedial role of financial development in corporate investment amid financing constraints and agency costs - Khan, Muhammad Kaleem; He, Ying; Kaleem, Ahmad; Akram, Umair; Hussain, Zahid (Journal of Business Economics and Management, 2018)
The study investigates the role of financial development in boosting the investment efficiency of firms’ investments in China. Using a large sample of firm-level financial data and country level economic data over the period 2004–2015, present study creates a link between financial and real economy. Firms are priori classified into under- or over-invested and effect of financial development is analyzed individually on each classification by using panel data estimations. The research concludes that firms suffering from under- (over-) investment problem due to financing constraints (agency problem), are more likely to increase (decrease) their investment` in the response of underlying financial development in the economy. This study has demonstrated a novel approach by concurrently incorporating the monitoring and financing issues that disturb the optimal level of investments. Moreover, the findings give strong implications by suggesting and empirically proving the remedy that has the potential to balance the investment distortions by rectifying monitoring and financing deficiencies.